2001
DOI: 10.1007/s002960100131
|View full text |Cite
|
Sign up to set email alerts
|

Systemic sclerosis complicated with nephrotic syndrome: relevance with antiribosomal P antibody

Abstract: The nephrotic syndrome is an extremely rare occurrence in systemic sclerosis (SSc). Here we describe a 39-year-old woman with SSc who developed the nephrotic syndrome along with the expression of antiribosomal P antibody but not of anti-double-stranded DNA antibody in her serum. Although a renal biopsy specimen showed minimal changes on light microscopy, immunofluorescence studies showed granular deposition of C3 and IgM in the glomeruli. The patient recovered from the nephrotic syndrome with the decrease in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Recent studies have suggested a direct participation of antiribosomal P antibody in the pathogenesis of lupus nephritis. 15,16 Hirohata et al 17 reported a case of SSc presenting with NS who tested positive for antiribosomal P antibody, which might have been involved in the development of NS. In this case, no such antibody was detected.…”
Section: Discussionmentioning
confidence: 97%
“…Recent studies have suggested a direct participation of antiribosomal P antibody in the pathogenesis of lupus nephritis. 15,16 Hirohata et al 17 reported a case of SSc presenting with NS who tested positive for antiribosomal P antibody, which might have been involved in the development of NS. In this case, no such antibody was detected.…”
Section: Discussionmentioning
confidence: 97%
“…Hirohata et al . also reported a 39-year-old female with SSc who developed nephrotic syndrome (minimal change disease) four years later and was treated successfully with 60 mg of oral prednisolone daily without recurrence [ 9 ]. In yet another case in 2017, a 12-year-old female was diagnosed with nephrotic syndrome (FSGS) as the first manifestation of juvenile SSc [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Renal involvement in SSc generally manifests with arterial hypertension with or without proteinuria. Although nephrotic syndrome has been reported in some SSc cases, it is rare and typically occurs due to amyloidosis or certain drugs rather than being directly linked to SSc [ 9 , 10 ]. Herein, we report a case of diffuse SSc complicated with nephrotic syndrome (focal segmental glomerulosclerosis) due to its rarity and for a better outlook in the management of these cases.…”
Section: Introductionmentioning
confidence: 99%
“…Antibodies to p25/p23 characterize a subset within the ACA-positive SSc patients, which is strongly associated with SjS symptoms (47). A case report of nephrotic syndrome in a patient with lcSSc and anti-ribosomal P antibodies was found (70). The association of anti-HMGCR antibodies and necrotizing autoimmune myositis (NAM) is wellknown (71,72).…”
Section: Autoabs In Sscmentioning
confidence: 99%